Knowledge, Attitude, and Practices of Practicing Dental Surgeons Towards Forensic Dentistry: Dental Surgeons Towards Forensic Dentistry - Khan, Nabeel; Aleem, Abdul; Bokhari, Samra; Naveed, Sanober; Haque, Munnawar Ul; Shirazi, Nauman (Pakistan Journal of Health Sciences, 2024)
Forensic dentistry and dental records are essential to the legal system and healthcare because they support human identification, individualized patient care, and court cases. Objective: To assess the knowledge, attitude, and practices of dental surgeons in Karachi towards forensic dentistry. Methods: A cross-sectional study was conducted among 227 practicing dental surgeons in Karachi, Pakistan. A purposive sampling technique was used to recruit dentists. Hence by obtaining informed consent participants' privacy was assured. The sample size was calculated using Open-Epi Software with an aim of 18% knowledge among practicing dental surgeons. Descriptive statistics were used for data analysis methods by using SPSS version 24.0. Results: The study's findings showed that of the 227 participants, 38.7% were female practicing dental surgeons and 61.3% were male. About 91.1% of active dental surgeons acknowledged the value of keeping dental records, 35% said that gender, and 20% said that race could be determined from dental records. Conclusions: The results of the study concluded that there was a favorable attitude toward forensic dentistry and its inclusion in the curriculum. Hence, further workshops, need to be conducted among practicing dental surgeons.